2020
DOI: 10.1101/2020.04.29.069054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spike mutation pipeline reveals the emergence of a more transmissible form of SARS-CoV-2

Abstract: This Version (2) corrects analysis that was based on the codon encoding Spike position 943; the apparent mutation at 943 was the result of a sequence error. The main conclusions of the paper regarding the mutation in Spike at 614 and recombination still hold. The key difference in version 2 is that we have removed the original figure 6, which was based on the 943 sequencing artifact, and instead moved a figure illustrating recombination that was independent of position 943 from the supplement into the main tex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
685
4
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(743 citation statements)
references
References 58 publications
37
685
4
17
Order By: Relevance
“…The wide breadth of domain arrangements along with the relatively small contact area between the S1 and S2 subunits observed here suggested that, despite a relatively low mutation rate, dramatic changes in S-protein structure may occur from few mutations. Indeed, recent evidence for a mutation in the SD2 to S2 contact region suggests a potential fitness gain for acquisition of such interfacial residues 29 . Based upon our results, this mutant, D614G, may indeed alter the conformational landscape of the SARS-CoV-2 S-protein.…”
Section: Discussionmentioning
confidence: 99%
“…The wide breadth of domain arrangements along with the relatively small contact area between the S1 and S2 subunits observed here suggested that, despite a relatively low mutation rate, dramatic changes in S-protein structure may occur from few mutations. Indeed, recent evidence for a mutation in the SD2 to S2 contact region suggests a potential fitness gain for acquisition of such interfacial residues 29 . Based upon our results, this mutant, D614G, may indeed alter the conformational landscape of the SARS-CoV-2 S-protein.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time some data both reviewed and unreviewed start to be available, suggesting that D614G on the Spike might provide some advantage to the virus. Bai (Bai et al 2020) and Brufsky (Brufsky 2020) observed a correlation of G614 with increased mortality, while Korber and coworkers (Korber et al 2020) found a correlation between the presence of the mutation and a higher viral load in patients.…”
Section: Time Series Of the Variable Sitesmentioning
confidence: 97%
“…During the preparation of this manuscript, we realized that some of the variants are also the topic of other papers and preprints predating this work e.g. (Korber et al 2020;Banerjee et al 2020;Somasundaram, Mondal, and Lawarde 2020;Begum et al 2020;Bai et al 2020;Yang et al 2020;Pachetti et al 2020). The fact that we identify some of the previously known mutations by using a different approach indicates that they represent a genuine signal rather than artefacts; however, this does not necessarily mean that their increase in time (see below) is a consequence of a correspondingly increased transmissibility rate or aggressiveness in general -for which at the moment there is no conclusive data as stated in most of the available preprints.…”
Section: Position 84 In Orf8mentioning
confidence: 99%
“…The NTD and RBD are better resolved in the cryo-EM density in the locked conformation than in the closed conformation ( Figure S3a), suggesting they are less mobile in this conformation. A SARS-CoV-2 variant which has now become the prevalent form globally contains a D614G mutation 26 which would abolish a salt bridge between D614 and K854 within the folded 833-855 motif (Figure S4b). This change could potentially destabilise the locked conformation to promote RBD opening and potentially increase virus receptor binding and membrane fusion activities.…”
Section: Structural Features Of Crosslinked Mutantsmentioning
confidence: 99%